Prognostic value of mitral valve regurgitation in patients with heart failure with mildly reduced ejection fraction - Abel, Noah; Behnes, Michael; Schmitt, Alexander; Reinhardt, Marielen; Lau, Felix; Abumayyaleh, Mohammad S. A.; Sieburg, Tina; Weidner, Kathrin; Ayoub, Mohamed; Mashayekhi, Kambis; Akın, Ibrahim; Schupp, Tobias (Hellenic journal of cardiology, 2025)
Background - Although mitral valve regurgitation (MR) is a common valvular heart disease in patients with heart failure (HF), there is a paucity of data on the characterization and outcomes of patients with HF with mildly reduced ejection fraction (HFmrEF) and concomitant MR. - Methods - From 2016 to 2022, consecutive patients hospitalized with HFmrEF (i.e., left ventricular ejection fraction from 41% to 49% and signs and/or symptoms of HF) were retrospectively included at one institution. Patients with MR were compared with patients without MR. Further risk stratification was performed according to MR severity and etiology (i.e., primary vs. secondary MR). The primary end point was all-cause mortality at 30 months (median follow-up), and the key secondary end point was hospitalization for worsening HF. - Results - Of 2181 patients hospitalized with HFmrEF, 59% presented with mild, 10% with moderate, and 2% with severe MR. MR was associated with increased all-cause mortality at 30 months (HR = 1.756; 95% CI 1.458-2.114; p = 0.001), with higher risk in more advanced stages. Furthermore, MR patients had higher risk of HF-related re-hospitalization at 30 months (HR = 1.560; 95% CI 1.172-2.076; p = 0.002). Even after multivariable adjustment, mild, moderate, and severe MR were still associated with all-cause mortality. Finally, the risk of all-cause mortality was lower in patients with secondary MR compared with patients with primary MR (HR = 0.592; 95% CI 0.366-0.956; p = 0.032). - Conclusion - MR is common in HFmrEF and independently associated with higher risk of all-cause mortality and HF hospitalization.